Characteristic features and mineralogical structure of diatomite from Ankara region of Turkey - Goren, R; Baykara, T; Marsoglu, M (MANEY PUBLISHING, 2001)
The present paper describes an investigation into the characteristic physical and chemical properties of, and the effect of sintering on, the mineralogical structure of diatomaceous earth mined in the Ankara region of Turkey. The material was found to consist predominantly of SiO2 (74.7%) and Al2O3 (14.55%). Analysis by X-ray diffractometry and other mineralogical analysis techniques showed the diatomite to he essentially amorphous with a small illite content. The material remained essentially unaltered lip to 850degrees C, but tit 1100degrees C cristobalite formed. Overall, the study confirmed that the diatomite deposit examined was somewhat lower in quality than material which is commercially available.
Keywords: Materials Science